Burden of undiagnosed and uncontrolled hypertension and its associated factors among rural populations in South Andaman Islands, India - Ramu, Manjunatha; Fatema, Ambreen; Ghosal, S. R.; Biji, Suma; Saida, K.; Mandal, Alok (International Journal Of Community Medicine And Public Health, 2023)
Background: Elevated BP is an important risk factor of cardiovascular diseases; undiagnosed and uncontrolled hypertension is a dangerous situation where target organ damage can occur leading morbidity and mortality in apparently healthy individuals. Therefore, with an aim to study the burden of undiagnosed and uncontrolled hypertension, this study with a cross sectional study design is undertaken in rural areas of South Andaman Islands. Methods: A community based cross sectional study. A total of 405 participants (Men: 175, Women: 230) were involved, mean age 48.36±15.16 years (Men: 50.69±16.01 years, Women: 46.58±14.26 years). Results: 30.4% of the participants reported that they are known hypertensives, and out of them only 63.41% were on regular treatment. 17.8% of the participants were first time diagnosed with hypertension during this study. Overall, 48.1% of participants are having hypertension (known hypertensives±newly diagnosed hypertensives), and only 63.20% of them know their status on hypertension. A large proportion are in Pre-hypertension status (52.04%). Conclusions: Almost half of the population are having burden of hypertension, and nearly 1/3rd of them do not know that they have hypertension; and among those who know the status, only 2/3rd of them are on regular treatment; and a large proportion of population is in pre-hypertension. We need to undertake rigorous efforts to unmask, diagnose and treat hypertension in the community.